(untitled) (Plant Tissue Culture and Biotechnology, 2012)
An efficient plant regeneration protocol was developed for Artemisia annua, an aromatic medicinal herb. Nodal explants inoculated on MS supplemented with 4.44 ?M BAP showed better growth response and produced 116.2 ± 0.1 micro-shoots of an average length 1.9 ± 0.3 cm after 35 days culture. The cluster of small shootlets were cultured on shoot elongation medium supplemented with 1.44 ?M GA3 and 10% coconut milk (CM) showed shoot elongation up to 4.6 ± 0.7 cm. Roots were induced after transfer to half strength MS supplemented with 2.46 ?M IBA produced 14.3 ± 0.2 roots with an average height of 4.3 ± 0.53 cm after 30 days. The rooted plantlets were transferred for hardening, 80 per cent of plantlets survived and resumed growth in the mixture of soil, vermiculite and farm yard manure (1 : 1 : 1). DOI: http://dx.doi.org/10.3329/ptcb.v22i1.11257 Plant Tissue Cult. & Biotech. 22(1): 33-39, 2012 (June)